Use of Continuous Intravenous Anakinra Infusion in Multisystem Inflammatory Syndrome in Children - Abdulaziz Alolayan; Abdullah S. Aldamegh; Azzah Alkhayrat (Case Reports in Critical Care)
Coronavirus disease (COVID-19) is an emergency pandemic with a high mortality rate worldwide. One of its complications in children is developing multisystemic inflammatory syndrome related to cytokine storm. Anakinra is a recombinant human interleukin-1 (IL-1) receptor antagonist used to suppress the exaggerated inflammatory response in such conditions, and it is potentially lifesaving in a cytokine storm. We present the case of a patient with critical COVID-19 associated with multisystem inflammatory syndrome in children (MIS-C) successfully treated with anakinra intravenous (IV) infusion.